Determination of Vanillin in Milk Powder by Rapid Column High Performance Liquid Chromatography - Li, Cheng; Zhao, Chang-Li (Asian Journal of Chemistry, 2014)
A rapid column high performance liquid chromatography method for the determination of vanillin in milk powder was studied. The vanillin was extracted from the sample with 40 % methanol by the ultrasonic extraction and then was purified by solid phase extraction with C18 cartridge. Vanillin was separated on a ZORBAX stable bound (4.6 × 50 mm, 1.8 mm) rapid chromatographic column with water-methonal (65:35) as mobile phase at a flow-rate of 2 mL/min and monitored with the photodiode array detector at 309 nm. The recoveries of the vinillin are 98-103 % and the relative standard deviations are 0.46-0.58 %. This method was applied to the determination of vanillin in milk powder with good results.